2014
DOI: 10.1016/j.foodres.2014.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive peptidomic and glycomic evaluation reveals that sweet whey permeate from colostrum is a source of milk protein-derived peptides and oligosaccharides

Abstract: Whey permeate is a co-product obtained when cheese whey is passed through an ultrafiltration membrane to concentrate whey proteins. Whey proteins are retained by the membrane, whereas the low-molecular weight compounds such as lactose, salts, oligosaccharides and peptides pass through the membrane yielding whey permeate. Research shows that bovine milk from healthy cows contains hundreds of naturally occurring peptides – many of which are homologous with known antimicrobial and immunomodulatory peptides – and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…Recently, we demonstrated that whey permeate is a good source of prebiotic milk oligosaccharides. 21,32,33 The massive industrial quantities of bovine dairy streams can make large-scale isolation of oligosaccharides possible. Therefore, whey permeate is considered to be a source of functional compounds for novel product development.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we demonstrated that whey permeate is a good source of prebiotic milk oligosaccharides. 21,32,33 The massive industrial quantities of bovine dairy streams can make large-scale isolation of oligosaccharides possible. Therefore, whey permeate is considered to be a source of functional compounds for novel product development.…”
Section: Resultsmentioning
confidence: 99%
“…Whey permeate, a low-value by-product obtained after whey proteins have been recovered, contains BMOs and has the potential to serve as a raw material for large-scale oligosaccharide isolation (Dallas et al 2014, Zivkovic & Barile 2011). Membrane filtration can be used to recover oligosaccharides present in whey permeate (Cohen et al 2017, de Moura Bell et al 2016), making these compounds more readily available as a functional food ingredient.…”
Section: Bovine Milk Oligosaccharides: Structures and Compositionmentioning
confidence: 99%
“…More recent investigations of whey permeate from bovine colostrum produced at the pilot scale by membrane filtration revealed almost 50 individual oligosaccharide compositions (Dallas et al, 2014). Out of the 50 oligosaccharides, 3′-sialyllactose ( 3′SL ), 6′-sialyllactose ( 6′SL ), and 6′-sialyllactosamine ( 6′SLN ) were the most abundant.…”
Section: Short Communicationmentioning
confidence: 99%